Key to the nests of Brazilian Epiponini wasps (Vespidae: Polistinae) - Arab, Alberto [UNESP]; Pietrobon, Thiago A.O. [UNESP]; Britto, Fábio B. [UNESP]; Rocha, Thalita [UNESP]; Santos, Luceli [UNESP]; Barbieri, Eduardo F. [UNESP]; Fowler, Harold G. [UNESP] (My University, 2003)
Brazil possesses the richest diversity of Epiponini wasps in the world. However, field identification of genera of these wasps, based on morphological features, is difficult without optical equipment. Therefore, this work presents a key to the Brazilian Epiponini genera based on the structural features of the nests.
Keywords: Field identification; Hymenoptera; Nest structure; Epiponini; Polistinae; Vespidae